Extracorporeal photopheresis as a promising strategy for the treatment of graft-versus-host disease after CAR T-cell therapy - Han, Huixiu; Wang, Lei; Ding, Yuntian; Neuber, Brigitte; Hückelhoven-Krauss, Angela; Lin, Min; Yao, Hao; Chen, Qian; Sauer, Tim; Schubert, Maria-Luisa; Guo, Zhiqiang; Müller-Tidow, Carsten; et al. (Blood advances, 2024)
Graft-versus-host disease (GVHD) occurs in about 10% to 33% of patients receiving “allogeneic” or “autologous” chimeric antigen receptor T (CAR-T) cells after preceding allogeneic hematopoietic stem cell transplantation (allo-HSCT) due to the substantial presence of alloreactive T cells. Extracorporeal photopheresis (ECP) shows promising clinical outcomes in the treatment of GVHD after allo-HSCT without hampering antitumor and antiviral effects. This raises an interesting question: whether ECP might constitute a new way to treat patients with GVHD after CAR T-cell therapy without compromising CAR-T cells significantly. Third-generation CD19-specific CAR-T cells were generated and an in vitro ECP protocol was established. The impact of ECP on CAR-T cells was comprehensively investigated in 2 models: the nondilution model reflects days after CAR T-cell infusion and the dilution model weeks after infusion. The therapeutic effect of ECP on GVHD was examined in an in vitro mixed lymphocyte reaction (MLR) assay. We found, ECP-treated CAR-T cells demonstrated reduced potency in inducing alloreaction compared with that of the group without ECP treatment in MLR assay. ECP could selectively induce apoptosis, thereby enriching the naive and central memory CAR-T cells with a reduced alloreactivity. The cytokine milieu of CAR-T cells could be switched from immune stimulation to immune tolerance in both models. Moreover, ECP could modulate the proliferative capacity of CAR-T cells without hampering their long-term functionality in the dilution model. In conclusion, ECP constitutes a promising treatment strategy for GVHD after allo-HSCT and CAR T-cell transfusion, as ECP reduces the alloreactivity without hampering CAR T-cell functionality.
Online veröffentlicht: 30. Mai 2024
Gesehen am 20.11.2024